FtsZ-Dependent Elongation of a Coccoid Bacterium - Pereira, Ana R. (mBio, 2016)
A mechanistic understanding of the determination and maintenance of the simplest bacterial cell shape, a sphere, remains elusive compared with that of more complex shapes. Cocci seem to lack a dedicated elongation machinery, and a spherical shape has been considered an evolutionary dead-end morphology, as a transition from a spherical to a rod-like shape has never been observed in bacteria. Here we show that a Staphylococcus aureus mutant (M5) expressing the ftsZ(G193D) allele exhibits elongated cells. Molecular dynamics simulations and in vitro studies indicate that FtsZ(G193D) filaments are more twisted and shorter than wild-type filaments. In vivo, M5 cell wall deposition is initiated asymmetrically, only on one side of the cell, and progresses into a helical pattern rather than into a constricting ring as in wild-type cells. This helical pattern of wall insertion leads to elongation, as in rod-shaped cells. Thus, structural flexibility of FtsZ filaments can result in an FtsZ-dependent mechanism for generating elongated cells from cocci.